Advances in the development of whole body computer simulation modelling of sports technique - King, M. A.; Yeadon, M. R. (Movement & Sport Sciences - Science & Motricité, 2015)
Computer simulation models have been used to address a range of research questions in sports biomechanics related to understanding the mechanics of sports movements, contributions to performance, optimisation of sports technique and control of sports movements. This paper will describe how theoretical models used in sports biomechanics have been developed at Loughborough University over the last 20 years, detailing their various components, subject-specific parameters, model evaluation, key findings and the strengths / limitations and how models could be further progressed in the future. With each model a four stage methodology has been used to answer specific research questions: development of the simulation model, determination of subject-specific parameters, evaluation of the model, and application of the model. These computer simulation models have provided insight into the mechanics behind sports movements that would not be possible through observing performance and have established the factors that limit optimal performance. In the future computer simulation models of sports movements will continue to develop in terms of sophistication to include elements such as joint compression and will provide further insight into the mechanics underlying sports movements.